“Control interno y su incidencia en el manejo operativo financiero del GAD municipal del cantón de Santo Domingo año 2018 – 2019”. - Gallo Canales, Jennifer Fernanda (2020)
This research was conducted at the Municipal GAD of the canton Santo Domingo to streng then internal control processes in operational management based on institutional planning in order to promote efficiency and efficiency in financial operations, providing a reasonable degree of security in each of the activities that are carried out. The purpose of this study was to assess the impact of internal control on the financial operational management of the municipal GAD of the Canton of Santo Domingo, 2018 – 2019; contribute to the appropriate solution and guidance of the financial processes to achieve institutional objectives, with the aim of improving poor communication between administrators and financial unit on the guide lines for each of the payment processes; lack of evidence and support in the documentation of the operations. For this reason, the methodology develops under the qualitative approach through these methods identified the findings found in the institutional operations. There sults obtained on the management of financial transactions represent significant weaknesses in the procedures, in addition to the evaluation of the system of control in the management of financial processes, in order to improve the critical points, found and finally the indicators were determined management to institutional targets for financial operations in order to identify proposals that improve the procedures for financial operations payments. Keywords: Internal Control, Operational - Financial Processes.